A new method for rapidly determining the strength qualification rate of a gelled material filling
Patent Information
- Application Number
- CN202611174991.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]然而,传统的胶凝材料强度测试通常需要等待7d或28d的养护周期才能进行,即:需要“养护至标准龄期后检测强度”才能对产品进行判定是否合格,该方法质量判定滞后,无法在充填作业过程中快速完成合格率判定,现场质控效率较低
[0027]本发明针对新型胶凝材料替代传统水泥的胶凝材料充填,通过“强度等价基准确立—单耗参数测定—投料吻合度验证”三步核心流程,实现充填体强度合格率的快速、高效判定,无需等待充填体完整养护周期,大幅缩短判定时间,适用于地下采矿充填作业质控管控等场景,兼顾判定准确性与实操便捷性。
Smart Images

Figure CN122889189A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cementitious materials technology, and specifically to a novel method for rapidly determining the pass rate of strength of cementitious material filling bodies. Background Technology
[0002] Cemented backfill is a type of single-slurry cemented backfill material and its application technology used in mining engineering. Traditional cemented backfill materials are made with rapid-hardening sulfoaluminate cement clinker as the cementing base, combined with quicklime activator and industrial waste. Cemented backfill technology, through material preparation, slurry transportation, and goaf dewatering and solidification processes, can control ground pressure activity and improve ore recovery rate.
[0003] In traditional cemented backfill materials, cement costs account for nearly 60% to 80% of the total cost. Furthermore, cement-cemented backfilling of entire tailings suffers from excessively large specific surface areas in fine and ultrafine tailings (typically <38μm and <10μm), leading to a combination of hydration competition, structural degradation, and low activity, resulting in low cementing efficiency and poor strength. Therefore, finding cement alternatives has become a major trend in mine cemented backfilling. Currently, new cementitious materials can reduce cement consumption by half under the same aggregate, concentration, and strength conditions. Their application in mine backfilling is a growing trend, reducing cement production, transportation, and consumption, thus decreasing industrial energy consumption and carbon emissions. Simultaneously, they can increase the capacity for tailings disposal, offering a significant cost-performance advantage under the current policy of "only reducing, not increasing" tailings dams.
[0004] However, traditional strength testing of cementitious materials usually requires a curing period of 7 days or 28 days before it can be carried out. That is, it is necessary to "test the strength after curing to the standard age" before the product can be judged as qualified. This method is lagging in quality judgment and cannot quickly complete the qualification rate judgment during the filling operation, resulting in low on-site quality control efficiency. Summary of the Invention
[0005] The purpose of this invention is to solve the aforementioned problems in the existing technology and provide a rapid method for determining the pass rate of strength of a novel cementitious material backfill. This invention targets cementitious materials that replace traditional cement for backfilling. Based on the key principle that the backfill mix ratio is the decisive factor in the strength and quality of the backfill, it achieves rapid and efficient determination of the pass rate of backfill strength through a three-step core process: "establishing a strength equivalence benchmark—measuring unit consumption parameters—verifying material compatibility." This eliminates the need to wait for the backfill to complete its curing cycle, significantly shortening the determination time. It is applicable to scenarios such as quality control and management of backfilling operations in underground mining, balancing accuracy and ease of operation.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows:
[0007] A novel method for rapidly determining the pass rate of strength of cementitious material filling bodies includes the following steps:
[0008] (1) Using cement-filled bodies as a reference, determine the strength equivalent mix ratio;
[0009] (2) Determine the unit consumption parameter under the strength equivalent ratio: Based on the strength equivalent ratio, determine the consumption of new cementitious materials required per unit volume of filling body, which is used as the unit consumption of the strength equivalent ratio;
[0010] (3) Determine the consistency of the strength equivalent ratio in the overall feeding:
[0011] S1. Determine the filling volume;
[0012] S2. Calculate the theoretical comprehensive feeding amount and theoretical comprehensive unit consumption of the new cementitious material for filling:
[0013] When using multi-strength-grade filling, the corresponding filling volumes for multiple strength grades within a certain period are as follows: V a V b V c ...V n The strength equivalent ratio unit consumption of the corresponding new cementitious materials are as follows: m a m b m c ...m n ,but:
[0014] The theoretical total feed rate is: M=V a ·m a +V b ·m b +V c ·m c +……V n m n ;
[0015] The theoretical comprehensive unit consumption m for filling during a certain period is:
[0016] m=(V a ·m a +V b ·m b +V c ·m c +……+V n ·m n ) / (V a +V b +V c +……+V n );
[0017] The formula for the actual comprehensive unit consumption of filling over a certain period of time is: Actual comprehensive unit consumption = Actual consumption of curing agent / Actual filling volume;
[0018] S3, Overall material feeding consistency = 1 + (actual overall unit consumption - theoretical overall unit consumption) / theoretical overall unit consumption;
[0019] (4) Rapid determination of the pass rate of strength of new cementitious material filling body:
[0020] According to the "Code for Acceptance of Construction Quality of Concrete Structures GB 50204-2015", and in conjunction with the requirements for mine backfilling quality, a qualified threshold for the overall material matching degree is set. If the overall material matching degree is within the qualified threshold range, the strength of the batch of new cementitious material backfill is deemed to meet the standard, and thus it is qualified; if the overall material matching degree is below the qualified threshold range, it is deemed to be substandard, and thus it is unqualified.
[0021] Furthermore, the novel cementitious material uses a curing agent produced by Guoyan Technology Development Co., Ltd., and selects P.O42.5 cement, slag powder produced by iron and steel smelting plants and composite active activators as raw materials. By using slag powder to replace part of the cement and supplementing it with an alkaline solid activator as the main component of the composite active activator, the hydration reaction activity of the slag powder is activated, thereby obtaining a novel low-cost filling cementitious material.
[0022] Furthermore, in step (1), the specific operation of determining the strength equivalent mix ratio is as follows: under the same conditions of whole tailings aggregate and 75% mass concentration, the 28-day strength of the PC 32.5R cement ash-sand ratio 1:8 test block is used as the criterion for judging whether the 28-day strength of the new cementitious material ash-sand ratio 1:16 test block is qualified, which is the strength equivalent mix ratio.
[0023] Furthermore, in step (2), based on the strength equivalence ratio, according to the actual filling strength, weigh the amount of new cementitious material, aggregate and water, prepare a standard volume of filling slurry, and count the consumption of new cementitious material; repeat the preparation of 3-5 sets of standard volume filling slurry, measure the consumption of new cementitious material in each set, and take the average value as the unit consumption of strength equivalence ratio.
[0024] Furthermore, in step (3) S1, the filling volume is determined by a combination of a three-dimensional laser scanner and a radar level gauge: the overall shape of the filling mine is measured by a three-dimensional laser scanner before filling and then reproduced by a three-dimensional software model. The area of any horizontal cross section of the filling is extracted by the model. The real-time filling height of the mine is obtained by a radar level gauge installed on the upper part of the mine. The radar level gauge transmits the filling height data of the mine to the surface filling station in real time through analog signals, and then the filling volume of the mine is extracted by combining the three-dimensional model of the mine.
[0025] Furthermore, in step (4), the qualified threshold for the overall material feeding consistency is set to 90%-110%.
[0026] The beneficial effects of this invention are as follows:
[0027] This invention addresses the use of novel cementitious materials to replace traditional cement in filling processes. Through a three-step core process of "establishing strength equivalence benchmarks, determining unit consumption parameters, and verifying material compatibility," it achieves rapid and efficient determination of the strength qualification rate of the filling body. It eliminates the need to wait for the filling body to complete its curing cycle, significantly shortening the determination time. It is applicable to scenarios such as quality control and management of filling operations in underground mining, balancing determination accuracy with ease of operation.
[0028] Compared to the traditional method of "testing strength after curing to the standard age," this invention eliminates the need for a 7-day or 28-day curing period. It allows for rapid strength qualification during the filling process, significantly improving on-site quality control efficiency and making it suitable for rapid adjustment during the filling process of various new cementitious materials. Furthermore, using cement filling as a reference ensures that the judgment criteria align with existing mine filling quality requirements. The method is simple to operate, low-cost, and suitable for judging the quality of various cementitious materials upon arrival at the site. Attached Figure Description
[0029] Figure 1 This is a curve comparing the material feeding consistency with the filling qualification rate. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the embodiments and accompanying drawings.
[0031] Example 1
[0032] A rapid method for determining the strength qualification rate of a novel cementitious material filling body is disclosed. The novel cementitious material uses a curing agent produced by Guoyan Technology Development Co., Ltd. Using the "strength of traditional cement filling bodies" as a reference benchmark, the method rapidly correlates the strength compliance status of the filling body with key parameters such as the range of the novel cementitious material, the strength-ratio-consumption relationship, and the strength qualification rate versus the consistency with the material input, thereby determining the qualification rate. The specific steps are as follows:
[0033] 1. Using cement filling as a reference, determine the strength equivalent mix ratio.
[0034] Using commonly used cement-filled materials as a reference system, the core objective is to establish the equivalent ratio between new cementitious materials and cement under the premise that "the strength of the filling material meets the standard", so as to provide a benchmark for subsequent judgment.
[0035] In accordance with the goal of reducing the unit consumption of the new cementitious material by half under the same aggregate, concentration, and strength conditions, and based on relevant research reports on mine backfilling technology and recent cement backfilling mix proportions, under the same conditions of whole tailings aggregate and 75% concentration, the 28-day strength of PC 32.5R cement with a cement-sand ratio of 1:8 is used as the criterion for determining whether the 28-day strength of the new cementitious material with a cement-sand ratio of 1:16 is qualified. This is known as the "strength equivalence ratio," which clarifies the equivalent dosage relationship between the new cementitious material and cement, and also serves as one of the main bases for determining the price of the cementitious material.
[0036] Through comparative experiments, the 28-day strength of the test block of the new cementitious material with a ash-sand ratio of 1:16 was set to be ≥ x MPa.
[0037] 2. Determine the unit consumption parameters under different strength equivalent ratios.
[0038] The unit consumption parameter is the core indicator for determining whether the amount of new cementitious material used meets the standard. Based on the strength equivalence ratio determined above, the consumption of new cementitious material required per unit volume of filling body with different filling ratios should be accurately measured as the standard for subsequent material feeding verification.
[0039] Based on the actual filling strength range, the strength of filling bodies with different mix proportions were measured in even multiples (the strength corresponding to this mix proportion range should be greater than the actual filling strength range). Mix proportions were: 1 / 6, 1 / 8, 1 / 10, 1 / 12, 1 / 14, 1 / 16, 1 / 18, and 1 / 20. The amounts of the new cementitious material, aggregate, and water were accurately weighed, and standard volumes of filling grout were prepared. The actual usage of each material was recorded, with a focus on the consumption of the new cementitious material, as shown in Table 1. Three to five sets of standard volumes of filling grout were prepared repeatedly, and the consumption of the new cementitious material in each set was measured. The average value was taken as the "strength-equivalent mix proportion unit consumption" (unit: kg / m³) to ensure the stability and accuracy of the unit consumption parameter and avoid the influence of single measurement errors on the judgment results. Environmental parameters (such as temperature and humidity) during the unit consumption measurement process were recorded to clarify the impact of environmental factors on unit consumption, facilitating subsequent auxiliary analysis.
[0040] Then, the strength equivalent unit consumption corresponding to a certain actual filling strength is determined by interpolation, as shown in Table 1: To determine the strength equivalent unit consumption m of cementitious material corresponding to a certain strength X=2MPa between strengths d and e, the interpolation method is used as follows:
[0041] m=107.74+(126.07-107.74)*(Xe) / (de)=107.74+(126.07-107.74)*(2-1.71) / (2.06-1.71)=122.95kg / m³.
[0042] Table 1. Test results of strength and unit consumption of new cementitious materials (curing agents) with different formulation ratios.
[0043]
[0044] 3. Determine the consistency of the strength-equivalent mix design with the overall material input.
[0045] The overall material feeding consistency is key to quickly determining the pass rate of the filling strength. By comparing the degree of consistency between the actual material feeding on site and the unit consumption of the strength equivalent ratio, it is directly related to whether the filling strength meets the standard, and thus the pass rate of the batch filling is determined. During on-site filling operations, the total volume of each batch filling and the actual total feeding amount of the new cementitious material are recorded in real time.
[0046] (1) The filling volume was determined by a combination of a three-dimensional laser scanner and a radar level gauge.
[0047] The overall shape of the filling site was measured by three-dimensional laser scanning before filling and then reproduced by three-dimensional software modeling. The area of any horizontal cross-section of the filling can be extracted from the model.
[0048] The real-time filling height of the stope is measured using a radar level gauge installed on the upper part of the stope. A radar level gauge suitable for high dust and strong vibration (IP68 protection rating, 0-60m range) is selected, capable of withstanding extreme environments with underground dust concentrations ≥1000mg / m³ and vibration frequencies ≤50Hz. The measurement error is controlled within ±0.5%, ensuring data accuracy. The sensor has an anti-interference algorithm to effectively filter the influence of dust and vibration on the signal. The radar level gauge must be fixed to a telescopic rod extending beyond the edge of the stope to eliminate the influence of protruding debris on measurement accuracy. The radar level gauge transmits the stope filling height data to the surface filling station in real time via analog signals.
[0049] After each shift's filling is completed and the dewatering is finished, the height of the stope before and after filling can be read by radar level gauge, and then the filling volume of the stope can be extracted by combining the three-dimensional model of the stope.
[0050] The formula for the actual comprehensive unit consumption of filling in a certain period is: Actual comprehensive unit consumption = Actual consumption of curing agent / Actual filling volume.
[0051] (2) Calculate the theoretical feed amount and theoretical comprehensive unit consumption for filling.
[0052] When using a single strength grade for filling, the formula is:
[0053] Theoretical feed rate = strength equivalent ratio unit consumption × total filling volume;
[0054] When using multi-strength-grade filling, as shown in Table 2, the corresponding filling volumes for strength grades a, b, and c over a certain period are as follows: V a V b V cThe corresponding cementitious material strength equivalent ratio unit consumption and unit consumption are respectively: m a m b m c ,but:
[0055] The theoretical total feed amount of cementitious materials is M=V a ·m a +V b ·m b +V c ·m c ;
[0056] The theoretical comprehensive unit consumption m for filling during a certain period is: m = (V a ·m a +V b ·m b +V c ·m c ) / (V a +V b +V c ).
[0057] When there are more than 3 filling strength grades, the same applies:
[0058] m=(V a ·m a +V b ·m b +V c ·m c +……+V n ·m n ) / (V a +V b +V c +……+V n );
[0059] Table 2. Calculation of Theoretical Consumption of Filling Cementitious Material (Curing Agent)
[0060]
[0061] (3) Overall material input consistency = 1 + (actual overall unit consumption - theoretical overall unit consumption) / theoretical overall unit consumption.
[0062] 4. Comparison curve of material feeding consistency and filling qualification rate
[0063] The mine conducted filling tests using two filling strength standards, 2MPa and 3MPa. The aforementioned tests showed that the corresponding theoretical unit consumption for filling was 122.95kg / m³ and 151.33kg / m³, respectively. After calculating the theoretical and actual comprehensive unit consumption for filling on the same day based on the filling volume of different strengths, the comprehensive material feeding consistency value for that day can be calculated. By comparing this with the 28-day strength qualification rate of filling (as shown in Table 3), the correlation between material feeding consistency and filling qualification rate can be seen.
[0064] Table 3. Inspection Table of Material Feeding Compatibility and Pass Rate at Filling Stations
[0065] To visually demonstrate the relationship between material feeding consistency and filling qualification rate, and to facilitate rapid on-site assessment, a comparison curve is plotted as follows: Figure 1 As shown, the curve is plotted with the material matching degree (%) on the horizontal axis and the filling qualification rate (%) on the vertical axis, which fits the actual filling quality control requirements.
[0066] Figure 1 The curves illustrate that: from day 1 to day 9, as the material feeding consistency increases, the filling qualification rate also increases; as the material feeding consistency decreases, the filling qualification rate also decreases. The filling qualification rate and the material feeding consistency values are close, and their fluctuation trends are consistent. From day 10 to day 12, when the filling material feeding consistency exceeds 100%, the filling qualification rate tends to be 100%. Overall, the experiment shows that when the filling material feeding consistency is above 90%, the filling qualification rate is above 90%.
[0067] Based on the variation patterns of the filling strength qualification rate and material feeding consistency obtained from the experiments, the filling strength qualification rate can be quickly determined by immediately testing the filling material feeding consistency. Referring to the "Code for Acceptance of Construction Quality of Concrete Structures GB50204-2015", a filling strength qualification rate requirement of ≥88% is set, corresponding to a filling material feeding consistency threshold range of 90%–110%, to ensure that the filling strength qualification rate is above 88%. If the material feeding consistency is below the threshold range, the material feeding amount needs to be increased promptly, and the cause (such as material metering error, slurry segregation, etc.) should be investigated. If it is above the threshold range, the filling cementitious material has been over-added, and the material feeding amount needs to be appropriately reduced.
[0068] This invention addresses the quality control needs of novel cementitious material filling bodies, overcomes the limitations of traditional judgment methods, balances practicality and technological breakthroughs, and fills the technological gap in rapid quality control of the strength of novel cementitious material filling bodies. Specifically, it is manifested as follows:
[0069] First, an innovative "strength equivalence benchmark" correlation model was established. This model abandons the complex process of establishing separate strength standards for traditional new cementitious materials. Instead, it uses the strength of existing cement backfill in mines as a reference, establishing a dosage benchmark for new cementitious materials through equivalent proportions. This eliminates the need to develop entirely new quality control standards, lowering the quality control threshold for the promotion and application of new cementitious materials. Simultaneously, it ensures that the judgment results are highly consistent with the existing backfill quality requirements in mines, solving the problem of the disconnect between new cementitious materials and traditional quality control systems.
[0070] Secondly, a combination of a 3D laser scanner and a radar level gauge is used to quickly and accurately determine the filling volume. The overall shape of the filling stope is measured using a 3D laser scanner before filling and then reconstructed using 3D software modeling. The area of any horizontal cross-section of the filling can be extracted from the model. The real-time filling height of the stope is measured by a radar level gauge installed on the upper part of the stope.
[0071] Third, it innovatively achieves a unity of "rapid judgment" and "precise correlation". Breaking through the bottleneck of the traditional "curing waiting + strength testing" lag, it uses the core logic of "unit consumption measurement + material feeding consistency calculation" combined with intelligent and precise monitoring of filling parameters. Through formula calculation and curve graph assistance, it directly correlates the strength compliance of the filling body with the on-site material feeding parameters. There is no need to wait for the 7-day or 28-day curing cycle. The preliminary judgment of the strength qualification rate can be completed simultaneously with the filling operation, which greatly improves the efficiency of on-site quality control and solves the problem that has always existed in the industry of the difficulty in balancing "rapid judgment" and "precision".
[0072] Fourth, through experimentation, a threshold range of 90%–110% for the consistency of filling material was determined to ensure a filling strength qualification rate of over 88%. If the consistency is below the threshold range, the amount of material added needs to be increased promptly, and the cause (such as metering error, slurry segregation, etc.) should be investigated. If it is above the threshold range, the filling cementitious material has been over-added, and the amount of material added needs to be appropriately reduced. This approach ensures the filling strength qualification rate while guiding the adjustment of the filling material amount, effectively controlling filling costs.
Claims
1. A rapid method for determining the pass rate of strength of a novel cementitious material filling body, characterized in that, Includes the following steps: (1) Using cement-filled bodies as a reference, determine the strength equivalent mix ratio; (2) Determine the unit consumption parameter of strength equivalent ratio: Based on the strength equivalent ratio, determine the consumption of new cementitious material required per unit volume of new cementitious material filling body, and use it as the unit consumption of strength equivalent ratio; (3) Determine the consistency of the strength equivalent ratio in the overall feeding: S1. Determine the filling volume; S2. Calculate the theoretical comprehensive feeding amount and theoretical comprehensive unit consumption of the new cementitious material for filling: When using multi-strength-grade filling, the corresponding filling volumes for multiple strength grades within a certain period are as follows: V a V b V c ...V n The strength equivalent ratio unit consumption of the corresponding new cementitious materials are as follows: m a m b m c ...m n ,but: The theoretical total feed rate is: M=V a ·m a +V b ·m b +V c ·m c +……V n m n ; The theoretical comprehensive unit consumption m for filling during a certain period is: m=(V) a ·m a +V b ·m b +V c ·m c +……+V n ·m n ) / (V a +V b +V c +……+V n ); S3, Overall material feeding consistency = 1 + (actual overall unit consumption - theoretical overall unit consumption) / theoretical overall unit consumption; (4) Rapid determination of the pass rate of strength of new cementitious material filling body: Referring to the "Code for Acceptance of Construction Quality of Concrete Structures GB 50204-2015" and in conjunction with the requirements for mine backfilling quality, a qualified threshold for the overall material matching degree is set. If the overall material matching degree is within the qualified threshold range, the strength of the batch of new cementitious material backfill is deemed to meet the standard, which is considered qualified; if the overall material matching degree is below the qualified threshold range, it is deemed to be unqualified.
2. The rapid determination method for the strength qualification rate of a novel cementitious material filling body according to claim 1, characterized in that: The novel cementitious material is made from P.O42.5 cement, slag powder produced by iron and steel smelting plants, and a composite active activator. The alkaline solid activator is used as the main component of the composite active activator to activate the hydration reaction activity of the slag powder, thereby obtaining the novel cementitious material.
3. The rapid determination method for the strength qualification rate of a novel cementitious material filling body according to claim 1, characterized in that: In step (1), the specific operation of determining the strength equivalent mix ratio is as follows: Under the same conditions of whole tailings aggregate and 75% mass concentration, the 28-day strength of the PC 32.5R cement ash-sand ratio 1:8 test block is used as the criterion for judging whether the 28-day strength of the new cementitious material ash-sand ratio 1:16 test block is qualified, which is the strength equivalent mix ratio.
4. The rapid determination method for the strength qualification rate of a novel cementitious material filling body according to claim 1, characterized in that, In step (2), based on the strength equivalence ratio, according to the actual filling strength, weigh the amount of new cementitious material, aggregate and water, prepare a standard volume of filling grout, and count the consumption of new cementitious material; repeat the preparation of 3-5 sets of standard volume filling grout, measure the consumption of new cementitious material in each set, and take the average value as the unit consumption of strength equivalence ratio.
5. The rapid determination method for the pass rate of filling strength of a novel cementitious material according to claim 1, characterized in that: In step (3) S1, the filling volume is determined by a combination of a three-dimensional laser scanner and a radar level gauge: the overall shape of the filling mine is measured by a three-dimensional laser scanner before filling and then reproduced by a three-dimensional software model. The area of any horizontal cross section of the filling is extracted by the model. The real-time filling height of the mine is obtained by a radar level gauge installed on the upper part of the mine. The radar level gauge transmits the filling height data of the mine to the surface filling station in real time through analog signals, and then the filling volume of the mine is extracted by combining the three-dimensional model of the mine.
6. The rapid determination method for the strength qualification rate of a novel cementitious material filling body according to claim 1, characterized in that: In step (4), the qualified threshold for the overall feeding consistency is set to 90%-110%.